Hubungan Power Otot Tungkai Dan Power Otot Lengan Terhadap Ketepatan Smash Bola Voli - Yeblo, Simson; Sugiono; Sukowati, Anton (Jurnal Muara Olahraga, 2024)
This type of research is a type of quantitative research with a correlational method. The research design used is the only posttest design. The research was carried out at the UNIMUDA Sorong volleyball court in November 2022. The population of this research was 13 UNIMUDA Sorong volleyball students. Based on the multiple correlation analysis, the calculated F-table was 5.045, then by consulting the F-table on db 2 versus 27 with a significance level of 5%, the F-table was obtained at 4.21 and the calculated F-table value was 5.45 which was greater than the F-table. Table 4.21 means that the multiple regression is significant. Thus, it can be concluded that there is a significant relationship between arm muscle strength and leg muscle strength on volleyball smash speed for UNIMUDA Sorong students.